2012
DOI: 10.1308/003588412x13171221498389
|View full text |Cite
|
Sign up to set email alerts
|

The impact of surgeon-based ultrasonography for parathyroid disease on a British endocrine surgical practice

Abstract: INTRODUCTION Surgeon-based ultrasonography (SUS) for parathyroid disease has not been widely adopted by British endocrine surgeons despite reports worldwide of accuracy in parathyroid localisation equivalent or superior to radiology-based ultrasonography (RUS). The aim of this study was to determine whether SUS might benefit parathyroid surgical practice in a British endocrine unit. METHODS Following an audit to establish the accuracy of RUS and technetium sestamibi (MIBI) in 54 patients, the accuracy of parat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 23 publications
1
14
1
Order By: Relevance
“…In a UK-based study, Aspinall et al. 15 found that surgeon-performed ultrasound had an accuracy of 86% in detecting the position of parathyroid adenomas in outpatient clinics. It should be borne in mind that apart from its value in localising primary parathyroid adenomas, 99m Tc-sestamibi-SPECT/CT is vital for identifying major parathyroid ectopias 16 and parathyroid glands in secondary hyperparathyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…In a UK-based study, Aspinall et al. 15 found that surgeon-performed ultrasound had an accuracy of 86% in detecting the position of parathyroid adenomas in outpatient clinics. It should be borne in mind that apart from its value in localising primary parathyroid adenomas, 99m Tc-sestamibi-SPECT/CT is vital for identifying major parathyroid ectopias 16 and parathyroid glands in secondary hyperparathyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…16 Recent interest in the merits of surgeon performed parathyroid ultrasonography has been evident. 17 It has been described in various studies as an appropriate method of parathyroid location and its accuracy has been compared with sestamibi imaging. [18][19][20] Apart from the low cost and non-invasiveness, it has been shown to provide accurate anatomic delineation of the adenomas relative to the thyroid gland, carotid artery and the clavicles, thereby facilitating a limited dissection.…”
Section: Discussionmentioning
confidence: 99%
“…9 The most recent studies demonstrate US as a single imaging modality to be equivalent or even more accurate than sestamibi, specifically when performed by a fellowship-trained radiologist or the surgeon. [10][11][12] In our study, US localized disease in nearly 75% of patients with an accuracy of 82%. These results are comparable to those obtained in other studies.…”
Section: Discussionmentioning
confidence: 54%